Religion: Functional and Dysfunctional, From Daily Life To Become Media Coverage - Warsono, Warsono; Alabyadh, Muhtadi (The Journal of Society and Media, 2022)
Religion cannot separate human life. In the history of civilization, religion grows from animism to monotheism. Religion has several functions, first it and legitimation for limitation of human capability. For this function, man needs the “Others” to solve their problem and explain why their problem occurs. The second, religion has a social identity function. The purpose of this research is to find out and ensure that religion is a symbol of social solidarity. This study uses the literacy method, which is the source of library data for books and journal articles. The last on Marxist view religion is an illusion, legitimation of bourgeois exploitation, but in the otherwise, religion has a social critic function and a theology of liberation.